Small diameter particle dispersion in a commercial aircraft cabin - Beneke, Jeremy Michael (Kansas State University, 2010)
Airline cabins represent an indoor environment in which the spread of particles or contaminants is of interest due to the large number of passengers and distances they travel. In fact, hundreds of millions of passengers travel each year spending extended periods in close proximity to one another. This close proximity causes concern about the spread of disease and contaminants amongst passengers. These passengers move from region to region of the world increasing the potential for worldwide epidemics. In an effort to understand the aircraft cabin environment and the dispersion of fine particles, an experimental study was conducted. The cabin used for the experiments is a simulated Boeing 767-300 with eleven rows, each comprised of seven seats. The particles release occurred in a short burst in all the seats across the second row simultaneously. This design focused on the longitudinal dispersion of particles throughout the cabin. The particles from this release had corrected aerodynamic diameters between 0.87 and 1.70 micrometers. The collection and analysis of data took place based on five criteria. The first analysis focused on the total particle counts at 27 locations throughout the cabin. The second analysis made use of a reference location for each of the tests and presents the exposure in each of those locations as a fraction of the reference during the same test. The third analysis centers its attention on the transient behavior as the particles were counted at various locations. The forth and fifth types of data analysis focus on the time required for each tested location to reach either 100 total particle counts or ten percent of the total seen at that location during that test. The tests show the regions close to the source experience higher levels of exposure, less time to reach the time limits, and higher levels of variation from test to test. The locations farther from the source show lower exposure levels, longer times to reach the limits, and less variation from test to test. This indicates the variations close to the source stem from the chaotic nature of the airflow rather than from irregularities of the dispersion system. The data agree well with previous work and suggest further studies would improve the understanding of the aircraft cabin environment and the spread of airborne particles and contaminants.
Keywords: aircraft; cabin; particle; contaminant; transport; indoor; Engineering, Aerospace (0538); Engineering, Mechanical (0548)